2015
DOI: 10.5271/sjweh.3530
|View full text |Cite
|
Sign up to set email alerts
|

Neurosensory and vascular function after 14 months of military training comprising cold winter conditions

Abstract: Results showed a quantifiable impaired neurosensory function and congruent symptom reports after 14 months of winter military training comprising cold winter conditions. The results suggest that prolonged exposure to cold impair sensory nerve function in the hands.Affiliation:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…However, in an earlier study we demonstrated that high-cumulative ambient cold exposure in the general population is positively related to symptoms of cold sensitivity, even in the absence of overt cold injury (Stjernbrandt et al 2017 ). A recently published study on heavily cold-exposed Swedish military conscripts showed a significant increase in symptoms of cold sensitivity after winter training, present also in subjects where no cold injury had been reported (Carlsson et al 2016 ). Earlier reports from the Falklands War revealed marked cold sensitivity in British servicemen with mild or even subclinical cases of cold injury (Thomas and Oakley 2001 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, in an earlier study we demonstrated that high-cumulative ambient cold exposure in the general population is positively related to symptoms of cold sensitivity, even in the absence of overt cold injury (Stjernbrandt et al 2017 ). A recently published study on heavily cold-exposed Swedish military conscripts showed a significant increase in symptoms of cold sensitivity after winter training, present also in subjects where no cold injury had been reported (Carlsson et al 2016 ). Earlier reports from the Falklands War revealed marked cold sensitivity in British servicemen with mild or even subclinical cases of cold injury (Thomas and Oakley 2001 ).…”
Section: Discussionmentioning
confidence: 88%
“…The experience of cold sensitivity is influenced by psychological factors (Carlsson et al 2010a ), and recent laboratory studies have shown a more pronounced pain response to a cold pressor test among individuals with high anxiety sensitivity (Dodo and Hashimoto 2017 ). Additionally, perception thresholds to cold and pain are often assessed by psychophysical methods, where the responses are modulated by psychological factors (Carlsson et al 2016 ). The present study did not include psychological variables, and this topic remains an important issue for further research.…”
Section: Discussionmentioning
confidence: 99%
“…These effects can be due to long‐term exposure to extreme cold air in the outdoor environment during cold season. Carlsson et al () also reported that the military participants exhibited reduced sensitivity to sensation of touch in body extremities after 14 months of military training in cold season. However, after short‐term exposure to cold environment, the control group showed lower finger skin temperatures and finger sensation levels than the case group.…”
Section: Discussionmentioning
confidence: 96%
“…I G U R E 6 The scatter plots of the cold strain index compared to finger skin temperature F I G U R E 7 The scatter plot of the finger sensation levels compared with finger skin temperatures F I G U R E 8 The scatter plot of the body fat percentage compared to BSAF I G U R E 9The finger sensation levels of two groups before and after cold exposure Before exposure to the extreme cold environment, the empirical baseline measurements showed the mechanic workers (case group) had lower sensation levels and finger skin temperature than the control group. These effects can be due to long-term exposure to extreme cold air in the outdoor environment during cold season Carlsson et al (2016). also reported that the military participants exhibited reduced sensitivity to sensation of touch in body extremities after 14 months of military training in cold season.…”
mentioning
confidence: 95%
See 1 more Smart Citation